2018
DOI: 10.1038/s41598-018-29790-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of HPV real-time PCR assay for the detection of HPV DNA in oral cytobrush and FFPE samples

Abstract: Specific HPV genotypes have been recognized as risk factors inducing head and neck cancers (HNC). The aim of this study was to validate a real-time PCR assay to detect accurately High Risk HPV DNA in Formalin Fixed Paraffin Embedded (FFPE) and oral cytobrush samples and compare the results with conventional PCR. Repeatability, reproducibility and limit of detection of Cobas assay were estimated for oral cytobrush and FFPE samples of patients with HNC. 53 samples of patients with a HNC were then used for assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
15
0
5
Order By: Relevance
“…The current gold standard for the viral load is qPCR. However, various PCR‐based quantitative methods such as qPCR‐enzyme immunoassay [35], TaqMan probes [36], fluorescence resonance energy transfer (FRET) probes [37], AllGlo probes [38], and more recently digital droplet PCR have been used for the detection and quantification of HPV DNA extracted from tissue samples [39]. Since the accurate limit of detection and limits of quantification of a PCR method mainly depend on the DNA extraction step, it is difficult to compare the detection limit of our method with others.…”
Section: Resultsmentioning
confidence: 99%
“…The current gold standard for the viral load is qPCR. However, various PCR‐based quantitative methods such as qPCR‐enzyme immunoassay [35], TaqMan probes [36], fluorescence resonance energy transfer (FRET) probes [37], AllGlo probes [38], and more recently digital droplet PCR have been used for the detection and quantification of HPV DNA extracted from tissue samples [39]. Since the accurate limit of detection and limits of quantification of a PCR method mainly depend on the DNA extraction step, it is difficult to compare the detection limit of our method with others.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that this method is very useful in HPV detection in FFPE tissue samples of HNSCC. The authors of these studies suggested that the higher efficiency of real‐time PCR in HPV detection in FFPE tissue samples is based on the amplification of short DNA fragments (31,43).…”
Section: Discussionmentioning
confidence: 99%
“…The current gold standard for viral load is qPCR. However, various PCR-based quantitative methods such as quantitative PCR-enzyme immunoassay [34], TaqMan probes [35], FRET probes [36], AllGlo probes [37], and more recently digital droplet PCR have been used for the detection and quantification of HPV DNA extracted from tissue samples [38]. Since the accurate limit of detection and limits of quantification of a PCR method mainly depend on the DNA extraction step, it is difficult to compare the detection limit of our method with others.…”
Section: Performance Verification Of Dna Purification Methodsmentioning
confidence: 99%